Navigate the Challenges of Simulation for Assessment: A Faculty Development Workshop - Megan A. Koster; Morgan Soffler (Association of American Medical Colleges, 2021)
Introduction Given barriers to learner assessment in the authentic clinical environment, simulated patient encounters are gaining attention as a valuable opportunity for competency assessment across the health professions. Simulation-based assessments offer advantages over traditional methods by providing realistic clinical scenarios through which a range of technical, analytical, and communication skills can be demonstrated. However, simulation for the purpose of assessment represents a paradigm shift with unique challenges, including preservation of a safe learning environment, standardization across learners, and application of valid assessment tools. Our goal was to create an interactive workshop to equip educators with the knowledge and skills needed to conduct assessments in a simulated environment. Methods Participants engaged in a 90-minute workshop with large-group facilitated discussions and small-group activities for practical skill development. Facilitators guided attendees through a simulated grading exercise followed by in-depth analysis of three types of assessment tools. Participants designed a comprehensive simulation-based assessment encounter, including selection or creation of an assessment tool. Results We have led two iterations of this workshop, including an in-person format at an international conference and a virtual format at our institution during the COVID-19 pandemic, with a total of 93 participants. Survey responses indicated strong overall ratings and impactfulness of the workshop. Discussion Our workshop provides a practical, evidence-based framework to guide educators in the development of a simulation-based assessment program, including optimization of the environment, design of the simulated case, and utilization of meaningful, valid assessment tools.